2020
DOI: 10.3390/jcm9072159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helicobacters in Neuropsychiatric Disease: A Systematic Review in Idiopathic Parkinsonism

Abstract: Interest in an aetiopathogenic role for Helicobacter in neuropsychiatric diseases started with idiopathic parkinsonism (IP), where the cardinal signs can be assessed objectively. This systematic review, using an EMBASE database search, addresses Oxford Centre for Evidence-Based Medicine based questions on the inter-relationship of Helicobacter and IP, the benefits of eradicating Helicobacter in IP and the outcome of not treating. The search strategy was based on Preferred Reporting Items for Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
(276 reference statements)
0
7
0
Order By: Relevance
“…According to the AMSTAR-2 criteria, 21 SRs [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] scored "critically low," 16 SR [13,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] scored "low," and 5 SR [36,[52][53][54][55] scored "moderate" (Figure 2). The most frequent drawbacks were as follows: no mentioning of the protocol in the systematic overview, no description of the rationale for the study designs included in the review, and no statement of funding for the included studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…According to the AMSTAR-2 criteria, 21 SRs [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] scored "critically low," 16 SR [13,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] scored "low," and 5 SR [36,[52][53][54][55] scored "moderate" (Figure 2). The most frequent drawbacks were as follows: no mentioning of the protocol in the systematic overview, no description of the rationale for the study designs included in the review, and no statement of funding for the included studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Because PD patients often have a degree of gut inflammation, faecal calprotectin is frequently raised ( Weis et al, 2019 ) and has been suggested as an early biomarker for PD risk ( Mulak et al, 2019 ). The GI abnormalities (particularly permeability issues and the finding of intestinal inflammation) found in PD are common to many other diseases, but their importance is that these changes may reflect pathophysiological processes that aggravate certain symptoms of PD ( Tucker et al, 2020a , Tucker et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…95 In addition, several reviews have specifically focused on the potential role of the bacterium Helicobacter pylori. 90,[99][100][101][102] The most recent meta-analysis 90 highlighted an increased risk of PD in subjects infected with this bacterium (pooled OR = 1.65 95% CI, 1.43-1.92, 9 studies published before 2019). Nevertheless, the benefit of its eradication on parkinsonian symptoms remains uncertain, 100 in particular in view of a recent randomized clinical trial showing no significant improvement in clinical outcomes at 12 and 52 weeks post-treatment.…”
Section: Previous Literature Regarding Pdmentioning
confidence: 99%
“…A significant number of literature reviews have recently been published regarding the link between certain pathogens and the onset of PD 89‐110 . Consequently, the objective here is not to provide an exhaustive description of the currently existing results, but to provide a brief summary of the pathogens investigated while presenting the most recent and relevant reviews.…”
Section: Do Studies In Humans Incriminate a Particular Pathogen?mentioning
confidence: 99%
See 1 more Smart Citation